Odpowiedzi

2010-03-04T21:04:39+01:00
1.
2a+(3a-7)=2a+3a-7=5a-7
x-(2x-3)=x-2x+3=-x+3
3x-(y-2x)=3x-y+2x=5x-y
-(3a+6)-4=-3a-6-4=-3a-10
Najlepsza Odpowiedź!
2010-03-04T21:05:25+01:00
A) 2a + (3a - 7)=2a+3a-7=5a-7
b)x- (2x-3)=x-2x+3=-x+3
c)3x - (y - 2x)=3x-y+2x=5x-y
d) -(3a + 6) - 4=-3a-6-4=-3a-10



a)
3x-y+x-1=4x-y-1
b)
3x-y+x-1+3x-y=7x-2y-1
c)
3x-y-x-1+3x-y=5x-2y-1
d)
3x-y(-x-1+3x-y)=3x-y+2x-1-y=5x-2y-1





a)a+(a-b) = a+a-b = 2a-b
b)2x-(x+4) = 2x-x-4 = x-4
c)7-(-x+6)=7+x-6 = 1+x
d)-(x+4)+(x-5) = -x-4 + x-5 = -9
e)1-(t+p)-(t-2) = 1-t -p-t+2 = 3-2t-p
f)-(-y+2)+(-2y-4) = y-2-2y-4=-y-6
2010-03-04T21:11:30+01:00
1
a)2a+(3a-7)=2a-3a+7= -a +7
b)x-(2x-3)=x+2x+3=3x+3
c)3x-(y-2x)=3x+y+2x=5x+y
d)-(3a+6)-4=-3a-6-4=-3a-10
2
A-(B-C)=3x-y-(x-1-(-3x-x))=3x-y-(x-1+3x+x)=3x-y+x+1-3x-x=-y+1
3
a) a+(a-b)=a+a-b=2a-b
b) 2x-(x+4)=2x+x-4=3x-4
c) 7-(-x+6)=7+x-6= 1+x
e) 1-(t+p)-(t-2)=1+t-p+t+2=2t+3-p
f) -(-y+2)+(-2y-4)=y-2-2y-4=-y-6